Effects of a monotonous tracking task on eye fixation related potentials - DAIMOTO, Hiroshi; YAGI, Akihiro; SUZUKI, Maya (Ningen kogaku. The Japanese journal of ergonomics, 1998)
The purpose of this experiment was to examine effects of a monotonous tracking task on eye fixation related brain potentials (EFRP). Ten subjects were assigned a monotonous task (96min) which was divided into 12 blocks. Each block consisted of a tracking task (5min) and a subjective questionnaire (3min). Eye movements and EEGs were measured during two probe tasks inserted before and after the monotonous task. EEGs were averaged at offset of saccades in order to obtain EFRP. As a result, error responses in tracking task, scores of feelings of fatigue and tedium increased, but scores of arousal and concentration decreased during the task. The most prominent positive component with latency of about 100ms in EFRP was compared between two probe tasks before and after monotonous task. The amplitude after the monotonous task decreased than before the task. The results suggested that EFRP was a useful index of the mental work load.